2012
DOI: 10.1371/journal.pone.0047722
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Streptococcus mutans: Dental Caries Onset Linked to Multiple Species by 16S rRNA Community Analysis

Abstract: Dental caries in very young children may be severe, result in serious infection, and require general anesthesia for treatment. Dental caries results from a shift within the biofilm community specific to the tooth surface, and acidogenic species are responsible for caries. Streptococcus mutans, the most common acid producer in caries, is not always present and occurs as part of a complex microbial community. Understanding the degree to which multiple acidogenic species provide functional redundancy and resilien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
461
2
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 439 publications
(503 citation statements)
references
References 74 publications
34
461
2
6
Order By: Relevance
“…When comparing the present study results with other studies, in considering the mild group relatively closer to the caries free groups as their mean dmft was (1.240, SD ± .970), some have the same a findings significant correlation between viable count of MS and dental caries index [35], [36], [31], [32], others have the opposite [37] due to the difference in the criteria been used or methods or the sample collection.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…When comparing the present study results with other studies, in considering the mild group relatively closer to the caries free groups as their mean dmft was (1.240, SD ± .970), some have the same a findings significant correlation between viable count of MS and dental caries index [35], [36], [31], [32], others have the opposite [37] due to the difference in the criteria been used or methods or the sample collection.…”
Section: Discussionsupporting
confidence: 47%
“…Different values of MS count in plaque and saliva was found in relation to the different stages of the caries, diet, and other types of involved bacteria [31], [32]. The higher count of MS bact.in early childhood will lead to higher DMF index at adulthood [33], so indicating the importance of monitoring the oral hygiene in childhood.…”
Section: Discussionmentioning
confidence: 99%
“…These species are found throughout the entire oral cavity, particularly on the tongue dorsum and in the saliva (Aas et al, 2005;Diaz et al, 2006;Mager et al, 2003). Gross et al, (2012) reported that among children without caries, the presence of Veillonella or other acid-producing species, including Streptococcus mutans, predicted the future development caries, suggesting that Veillonella levels are sensitive clinical bioindicators and early warning signs of acid production. Therefore, when determining methods for treating or preventing oral infectious diseases in children, it is important to understand the distribution and frequency of Veillonella species in oral biofilms.…”
Section: Issn: 2319-7706 Volume 6 Number 7 (2017) Pp 449-461mentioning
confidence: 99%
“…In the case of dental caries, Veillonella species are highly associated with lactic acid-producing species (46). This is not surprising given its reliance on lactate as a nutrient source.…”
mentioning
confidence: 99%